2018
DOI: 10.1590/0102-672020180001e1356
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Anxiety, and Binge Eating Before and After Bariatric Surgery: Problems That Remain

Abstract: Background: As the number of surgeries increases and the elapsed time of the realization increases as well, the postoperative evaluations would become increasingly necessary. Aim: To assess the psychological profile before and after surgery. Methods: Were evaluated 281 patients from the public service of bariatric surgery. In this study, 109 patients completed the evaluations before surgery (T0) and up to 23 months after surgery (T1); 128 completed the evaluations in T0 and between 24 months and 59 months afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
2
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 21 publications
(24 reference statements)
2
37
2
7
Order By: Relevance
“…There were nine studies that collected their follow‐up data at around 24 months post‐surgery. Eight out of these nine studies reported a reduction in depression symptoms from pre‐surgery, but one study found that pre‐surgery depression symptoms remained the same at 24‐month follow‐up . Two of these studies used clinical assessments and found an overall reduction of people with depression, whereas one did not …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were nine studies that collected their follow‐up data at around 24 months post‐surgery. Eight out of these nine studies reported a reduction in depression symptoms from pre‐surgery, but one study found that pre‐surgery depression symptoms remained the same at 24‐month follow‐up . Two of these studies used clinical assessments and found an overall reduction of people with depression, whereas one did not …”
Section: Resultsmentioning
confidence: 99%
“…Six studies conducted RYGB or GBY, and six used LAGB . Other studies used SG, BPD/DS, VG, and GB, but these were not very commonly used, and they found similar outcomes to other surgery options.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In most current literature, improved long-term depression outcomes among BS patients have been shown, although some studies have not demonstrated improvement and others have revealed worsening [9][10][11]. However, little is known about the impact that the diagnosis of depression before bariatric surgery (DDBS) may have on weight loss.…”
Section: Introductionmentioning
confidence: 99%